2017
DOI: 10.1016/j.je.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Age-, sex-, and diagnosis-specific incidence rate of medically certified long-term sick leave among private sector employees: The Japan Epidemiology Collaboration on Occupational Health (J-ECOH) study

Abstract: BackgroundLong-term sick-leave is a major public health problem, but data on its incidence in Japan are scarce. We aimed to present reference data for long-term sick-leave among private sector employees in Japan.MethodsThe study population comprised employees of 12 companies that participated in the Japan Epidemiology Collaboration on Occupational Health Study. Details on medically certified sick-leave lasting ≥30 days were collected from each company. Age- and sex-specific incidence rate of sick-leave was cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 16 publications
5
22
0
2
Order By: Relevance
“…younger males is in line with prior reports [16,18,21], and the opposite trend among the older age group is likely due to a disproportionate survival effect among female vs. male employees.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…younger males is in line with prior reports [16,18,21], and the opposite trend among the older age group is likely due to a disproportionate survival effect among female vs. male employees.…”
Section: Discussionsupporting
confidence: 91%
“…For example, employees at the participating companies can use paid sick; they are paid over two-thirds of their salary for the maximum length of 2.5 -3.9 years. Details of the cohort are available elsewhere [16].…”
Section: Study Populationmentioning
confidence: 99%
“…24 Therefore, it is important to investigate the association in this particular population. Third, evidence on this subject is scarce in working populations; depression is the leading cause of sick-leave among working populations in Japan 25 and other developed countries. 26,27 To address these issues, we aimed to examine the prospective association of the HLI, which is composed of seven modifiable lifestyle factors (including body mass index [BMI], leisure-time physical activity, smoking, alcohol intake, vegetable intake, fruit intake, and sleep duration), with depressive symptoms in a Japanese working population.…”
Section: Introductionmentioning
confidence: 99%
“…Mental health diseases are an important cause of long-term sick leave. A multi-center occupational cohort study in Japan showed that mental illness was the most common reason for men aged 20–59 yr and women aged 20–49 yr to take sick leave for 30 d or more3 ) . Additionally, a cohort study in Sweden showed that more than 90 d of absenteeism due to psychiatric disorders affects all-cause and cause-specific mortality4 ) .…”
Section: Introductionmentioning
confidence: 99%